Morocco : Selected Issues. (IMF Staff Country Reports; Country Report, 1997)
Contents include: basic data and social demographic indicators, 1971-95. Liberalizing the economy structural reform issues: reform of the fiscal system; public enterprise reform and increased scope for private sector activity; price liberalization and reform of consumer subsidies; environmental issues; financial sector; factor markets; and exchange system liberalization. Labor market developments; recent trends; structure of unemployment; reasons for unemployment; reforming labor markets. Determinants of nongovernment investment, 1972-95: nongovernment investment data; estimates of investment functions; explaining the performance of nongovernment investment. The associaiton agreement and the new fisheries agreement between Morocco and the EU. Statistical tables.